EFEKTIVITAS PENEGAKAN HAK ASASI MANUSIA DALAM HUKUM POSITIF INDONESIA - Darmawati, Darmawati (Universitas Nurul Jadid, 2025)
The enforcement of human rights is a fundamental aspect of a democratic state that upholds the principles of justice and the welfare of its citizens. In Indonesia, human rights are guaranteed by the 1945 Constitution and various laws and regulations, but their implementation in practice faces numerous challenges. The aim of this research is to analyze the implementation of human rights enforcement within Indonesia's positive law, focusing on the obstacles, challenges, and efforts made by the state and relevant institutions. The methodology used in this study is a qualitative approach with descriptive analysis that explores the applicable regulations, law enforcement mechanisms, and human rights violations occurring in Indonesia. This study finds that although Indonesia has various legal instruments to protect human rights, these instruments are hindered by several factors, including inconsistencies between laws and practices in this area, weak law enforcement, and the ongoing occurrence of human rights violations. It is clear that the enforcement of human rights continues to be obstructed by widespread discrimination and impunity within the legal system. The study concludes that to create a better environment for the enforcement of human rights in Indonesia, improvements are needed in the legal system, the enhancement of law enforcement agencies' capacities, and an increase in public awareness and participation.